Inclusive Learning Device Development Strategy Based on UDL and Differentiation for Children with Special Needs in Indonesia - Sheeva Ziyana; Marfuah Marfuah; Abdur Rahmani; Yosi Armelia (Universitas Negeri Surabaya, 2025)
Inclusive education is an approach that ensures right every children , including children with needs Special (ABK), for get equal education​ in environment the same learning . However , the implementation Still face various challenges , especially in provision device adaptive and responsive learning​ to need individual . Article This aiming For identify development strategies device effective learning​ for ABK in inclusive settings . Research This done through systematic literature review method journal scientific , policy education and studies case from various countries between 2018 to 2023. Analysis​ done use PRISMA framework , with focus on three component main : planning learning based on individual needs , development adaptive teaching materials , and implementation of multimodal learning media . The results of the study show that integration Universal Design for Learning (UDL) principles with differentiation strategies learning capable increase engagement and results learn ABK in a significant . Besides that , the application of learning media based on technology as well as approach collaborative between regular teachers and assistant teachers become factor key in realize environment inclusive and meaningful learning . Findings​ This give contribution important to development policies and practices education more inclusive​ structured and sustainable in Indonesia. It is recommended that the strengthening of teacher capacity and provision of learning media banks inclusive become priority in support success education for all child .